Creativity and innovation in research: the perceptions of Malaysian postgraduate students / Faizah Abd Majid. - Abd Majid, Faizah (Universiti Teknologi MARA Cawangan Selangor, 2010)
The 21st century global market demands a highly skilled workforce that is intellectually active, creative, innovative, articulate, adaptable and capable of critical thinking. Consequently, Malaysian higher education institutions of the 21st century will have the responsibility to ensure the targets are achived (Ministry of Higher Education Strategic Plan Report, 2007). Some strategies have been suggested by the Ministry of Higher Education to achieve the targets of producing researchers who are creative and innovative. This research sought to investigate the perceptions of Malaysian postgraduates on creativity and innovation in research. A survey of a selected group of postgraduates based on a convenience sampling technique was carried out to elicit relevant data. Quantitative data was analysed and presented in terms of means and percentages. Descriptive data was analysed thematically and categorised. The findings revealed that the respondents were aware of the national higher education agenda on enhancing research and innovation. Likewise, they were able to provide descriptions of creative and innovative researchers. However, they indicated that much more could be done in higher education institutions in order to prepare them to become creative and innovative researchers. Their suggestions include revising the curriculum in particular the content, assignments and assessment. Most importantly, they highlighted the need to include them as key players in research activities and to participate globally. These findings have direct implications for higher education policy makers, curriculum designers and postgraduate instructors.